Plant species richness promotes soil carbon and nitrogen stocks in grasslands without legumes - Cong, Wen‐Feng; Ruijven, Jasper; Mommer, Liesje; De Deyn, Gerlinde B; Berendse, Frank; Hoffland, Ellis; Lavorel, Sandra (The Journal of ecology, 2014)
The storage of carbon (C) and nitrogen (N) in soil is important ecosystem functions. Grassland biodiversity experiments have shown a positive effect of plant diversity on soil C and N storage. However, these experiments all included legumes, which constitute an important N input through N₂‐fixation. Indeed, the results of these experiments suggest that N₂ fixation by legumes is a major driver of soil C and N storage. We studied whether plant diversity affects soil C and N storage in the absence of legumes. In an 11‐year grassland biodiversity experiment without legumes, we measured soil C and N stocks. We further determined above‐ground biomass productivity, standing root biomass, soil organic matter decomposition and N mineralization rates to understand the mechanisms underlying the change in soil C and N stocks in relation to plant diversity and their feedbacks to plant productivity. We found that soil C and N stocks increased by 18% and 16% in eight‐species mixtures compared to the average of monocultures of the same species, respectively. Increased soil C and N stocks were mainly driven by increased C input and N retention, resulting from enhanced plant productivity, which surpassed enhanced C loss from decomposition. Importantly, higher soil C and N stocks were associated with enhanced soil N mineralization rates, which can explain the strengthening of the positive diversity–productivity relationship observed in the last years of the experiment. Synthesis. We demonstrated that also in the absence of legumes, plant species richness promotes soil carbon (C) and nitrogen (N) stocks via increased plant productivity. In turn, enhanced soil C and N stocks showed a positive feedback to plant productivity via enhanced N mineralization, which could further accelerate soil C and N storage in the long term.